Adverse reactions to metal debris occur with all types of hip replacement not just metal-on-metal hips: a retrospective observational study of 3340 revisions for adverse reactions to metal debris from the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man. Issue 1 (December 2016) - Matharu, Gulraj; Pandit, Hemant; Murray, David; Judge, Andrew
Abstract Background Adverse reactions to metal debris (ARMD) have resulted in the high short-term failure rates observed with metal-on-metal hip replacements. ARMD has recently been reported in non-metal-on-metal total hip replacements (non-MoM THRs) in a number of small cohort studies. However the true magnitude of this complication in non-MoM THRs remains unknown. We used a nationwide database to determine the risk of ARMD revision in all non-MoM THRs, and compared patient and surgical factors associated with ARMD revision between non-MoM and MoM hips. Methods We performed a retrospective observational study using data from the National Joint Registry for England, Wales, Northern Ireland and the Isle of Man. All primary hip replacements undergoing revision surgery for ARMD were included (n  = 3, 340). ARMD revision risk in non-MoM THRs was compared between different commonly implanted bearing surfaces and femoral head sizes (Chi-squared test). Differences in patient and surgical factors between non-MoM hips and MoM hips revised for ARMD were also analysed (Chi-squared test and unpairedt -test). Results Of all ARMD revisions, 7.5% (n  = 249) had non-MoM bearing surfaces. The relative risk of ARMD revision was 2.35 times (95% CI 1.76–3.11) higher in ceramic-on-ceramic bearings compared with hard-on-soft bearings (0.055 vs. 0.024%;p  < 0.001), and 2.80 times (95% CI 1.74–4.36) higher in 36 mm metal-on-polyethylene bearings compared to 28 mm and 32 mm metal-on-polyethylene bearings (0.058 vs. 0.021%;p  < 0.001). ARMD revisions were performed earlier in non-MoM hips compared to MoM hips (mean 3.6-years vs. 5.6-years;p  < 0.0001). Non-MoM hips had more abnormal findings at revision (63.1 vs. 35.7%;p  < 0.001), and more intra-operative adverse events (6.4 vs. 1.6%;p  < 0.001) compared to MoM hips. Conclusions Although the overall risk of ARMD revision surgery in non-MoM THRs appears low, this risk is increasing, and is significantly higher in ceramic-on-ceramic THRs and 36 mm metal-on-polyethylene THRs. ARMD may therefore represent a significant clinical problem in non-MoM THRs.